1989
DOI: 10.1002/bip.360280505
|View full text |Cite
|
Sign up to set email alerts
|

The 9‐fluorenylmethyloxycarbonyl group as a 5′‐OH protection in oligonucleotide synthesis

Abstract: Oligo-DNAs are synthesized on a solid support using the 9-fluorenylmethyloxycarbonyl group as a 5'-OH base labile protection. The synthesis of the pure protected nucleotides, a relevant phosphoramidite-type strategy of coupling, and the optimization of the deprotection steps are described. This new synthetic method is an alternative to the standard protocol that avoids acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…As part of these initial studies, we also investigated the effect of the capping step on solid-phase assembly using the Fmoc phosphoramidites, since other studies reported an instability of Fmoc to (dimethylamino)pyridine (Ma & Sonveaux, 1989;Webb & Matteucci, 1986;Kuijpers et al, 1990), the capping catalyst used in our synthesizer. We conducted additional syntheses of the unmodified 6-mer and the AAF-6-mer by excluding the capping step from the standard CED cycle.…”
Section: Solid-phase Synthesis Of D(tttgtt) and D[tt-mentioning
confidence: 99%
“…As part of these initial studies, we also investigated the effect of the capping step on solid-phase assembly using the Fmoc phosphoramidites, since other studies reported an instability of Fmoc to (dimethylamino)pyridine (Ma & Sonveaux, 1989;Webb & Matteucci, 1986;Kuijpers et al, 1990), the capping catalyst used in our synthesizer. We conducted additional syntheses of the unmodified 6-mer and the AAF-6-mer by excluding the capping step from the standard CED cycle.…”
Section: Solid-phase Synthesis Of D(tttgtt) and D[tt-mentioning
confidence: 99%
“…The first Fmoc-amino acid was incorporated into both resins using the symmetrical anhydride in the presence of catalytic amounts of DMAP, while DIPCDI-OxymaPure was used for the rest of the residues . The symmetrical anhydride was a satisfactory method for introducing the first amino acid on the OH-BTL resin (Table ), as demonstrated by means of UV analysis of the piperidine–dibenzofulvene adduct . The peptide content of the final peptide resin calculated by amino acid analysis (AAA) was shown to be superior for the OH-BTL resin for all three peptides (Table ).…”
mentioning
confidence: 99%
“…After each chain elongation using 98, the Fmoc group is removed in basic media such as Et 3 N/py [130],piperidine/MeCN (5:95) [34],morpholine/MeCN (3:7) [34], or 0.1 M DBU/MeCN [132] to give 99 (Scheme 51). In this deprotection, the efficacy has been studied by varying the combination of base and solvent [131]; it is concluded that DBU/MeCN (or py) is the best combination.…”
Section: Trocoõ B~oallylmentioning
confidence: 98%
“…The base-catalyzed fragmentation of the Fmoc group is explained by an initial removal of the H-9 atom, which is acidic in nature (Scheme 50). A problem remaining in this protection is the liberation of highly reactive dibenzofulvene [131]. In the actual synthesis of ribonucleotides, the Fmoc group is introduced by treatment of alcohols with Fmoc chloride (Fmoc-Cl) (see 96~97) [132], and the resulting 5'-carbonates are phosphitylated (see Sect.…”
Section: Trocoõ B~oallylmentioning
confidence: 99%